Developing Word Wall Game Worksheet in Reading Narrative Text at SMA Negeri 3 - Lubis, Kharinnisa Rohimah; Harahap, Neni Afrida Sari (Universitas Negeri Medan, 2024)
This research aimed to develop a Word Wall Game Worksheet in reading narrative text for tenth-grade students. The research method used the Research and Development (R&D) design from Borg and Gall (2003) with six steps, namely Gathering Data and Information, Need Analysis, Product Design, Validation to Experts, Revising Products, and Final Products. The research subjects consisted of 34 students in class X-11 and one English Teacher at SMA Negeri 3 Medan. The data collection techniques included interviews and questionnaires. The data analysis techniques included Organizing and preparing data for analysis, investigating the data, Coding, Interpretation, Confirmation, and the Last step to write an inclusive description of the resulting analysis. The result of the study showed that the development of the Word Wall Game Worksheet was suitable and approved for use by tenth-grade students in reading narrative text provided by the scores validation of the products given by the experts from the lecturer was 91% and the teacher was 90%. The final products were in the form of a Word Wall Game Worksheet integrated with the wordwall.net platform and the learning material was in the form of a handbook.